Confined Bilayers Passively Regulate Shape and Stress - Staykova, Margarita; Arroyo, Marino; Rahimi, Mohammad; Stone, Howard A. (Physical review letters, 2013)
Lipid membranes are commonly confined to adjacent subcellular structures or to artificial substrates and particles. We develop an experimental and theoretical framework to investigate the mechanics of confined membranes, including the influence of adhesion, strain, and osmotic pressure. We find that supported lipid bilayers respond to stress by nucleating and evolving spherical and tubular protrusions. In cells, such transformations are generally attributed to proteins. Our results offer insights into the mechanics of cell membranes and can further extend the applications of supported bilayers.